ANALISIS PENGETAHUAN PROSEDURAL SISWA KELAS SMP PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI GAYA KOGNITIF - Rafieq Badjeber; Wahyuni H Mailili (Universitas Sultan Ageng Tirtayasa, 2018)
This research aims to describe student’s procedural knowledge on system of two linear equations in two variable that reviewed from cognitive styles. The research is descriptive with qualitative approach. The subject of this research were 8 student’s of grade VIII SMPN 1 Palu consisting of 4 students field independent and 4 students field dependent. The results showed that students with cognitive styles field independent were able to apply the appropriate procedure correctly and verify the procedure using symbol or mathematical model but don’t able to modify the procedure to handle the factors in problem solving. Whereas students with cognitive styles field dependent are not capable to apply the appropriate procedure correctly, verify the procedure using symbol or mathematical model and modify the procedures to deal with factors in problem solving. Keywords: Procedural Knowledge, System of Linear Equations in Two Variable, Cogntive Styles.